P-A4 Multimodal theranostic tests for antiretroviral drug delivery. (April 2018) - Kevadiya, Bhavesh; Woldstad, Christopher; Ottemann, Brendan; Dash, Prasanta; Sajja, Balasrinivasa; Lamberty, Benjamin; Morsey, Brenda; Kocher, Ted
Abstract : Abstract: Long acting slow effective release antiretroviral therapy (LASER ART) was developed to improve patient regimen adherence, prevent new infections and facilitate drug entry into human immunodeficiency viral reservoirs. To speed LASER ART development "multimodal imaging theranostic nanoprobes" were created. These europium (Eu3+ ) doped cobalt ferrite (CF) dolutegravir (DTG) (EuCF-DTG) nanoparticles were used as platforms for drug-particle biodistribution. After parenteral injection of EuCF-DTG, to rats and rhesus macaques, measured drug and cobalt levels by florescence and magnetic resonance imaging tests were found to be coordinate to iron levels. Moreover, EuCF-DTG was found to be a log order-of-magnitude more sensitive than equivalent amounts of particle encased iron oxide. Folic acid decoration facilitated drug particle cell uptake. We posit that theranostic nanoprobes can facilitate LASER ART drug delivery and be used as part of a precision nanomedicine treatment strategy.